PENGEMBANGAN MEDIA BIG BOOK DENGAN MODEL TPACK UNTUK MENINGKATKAN KEMAMPUAN LITERASI MENULIS CERITA RAKYAT KELAS V SD NEGERI 102 PALEMBANG - Zuleha , Anisa; Wardiah, Dessy; Pratama, Aldora (Study program PGSD FKIP Universitas Bung Hatta, 2025)
The purpose of this study is to produce a Big Book product based on folklore for grade v students of SD Negeri 102 Palembang that valid, practial and effective. This study uses the ADDIE method wich goes trough 5 stages (Analysis, Design, Development, Implementation, dan Evaluation). The researcher uses the TPACK (Technological Pedagogical Content Knowledge) method to produce to product that can be accessed via mobile phones, laptops, computers and notebooks, and has pedagogical value. The results of validity analysis are based on the results of expert validation, questionnaires and documentation. Media expert validation got a percentage og 80%, material validation got 85% and language validation got 95%, so Big Book media was categorized as very valid for use with revisions. The results of the researcher’s practicality were obtained from students through one to one and small group trials. The results of the one to one researcher got a percentage of 93,88% and the small group tiral got 92,21%, so the Big Book media is very practical to use. The validity results obtained by researchers from the field test, researchers obtained a percentage of 95,33% with a very effective category. Thus, the Big Book media meets the criteria of valid, practical and effective and is worthy of use in learning.